EFFECTS OF TWO METACOGNITIVE STRATEGIES ON ACHIEVEMENT OF JUNIOR SECONDARY SCHOOL STUDENTS IN ALGEBRA IN ONITSHA EDUCATION ZONE (NAU Journal of Technology and Vocational Education, 2024)
This study investigated the effect of graphical organizer and metacognitive reading on Juniorsecondary school two (JSS2) students’ academic achievement in algebra in Onitsha EducationZone of Anambra State. One research question guided the study and one null hypothesis weretested at 0.05 alpha level A quasi experimental research design, specifically, pre-test, post-testnon-equivalent control design was used. The population of the study consists of 4,433 JSS2students while 150 students formed the sample size. The sample technique employed was multistage sampling. The research instrument used for data collection was the mathematicsachievement test. The instrument was validated by three experts and Kuder RichardsonFormula 20 was used to ascertain the reliability coefficient at 0.87. Mean, standard deviationand analysis of covariance were used for data analysis. The findings of the study showed thatstudents taught algebra using Graphic Organizer and metacognitive reading strategiessignificantly achieved more than those taught with traditional method and students taughtalgebra using graphic organizer achieved significantly higher than those taught usingconventional method of teaching. It was recommended among others that in-servingmathematics teachers should be trained by government and ministry of education on the use ofgraphic organizer and metacognitive reading strategies through workshops, seminars.
Keywords: Algebra, Achievement, metacognitive, strategies